Analisis Penerapan Manajemen Risiko Berbasis ISO 31000:2018 pada UMKM dalam Industri Slow Fashion : Studi Kasus OUR DéJAHOE - Nilam Meylani; Salsha Dwi Agustien; Maisya Hayina Zahra; Rahma Khairunnisa Amalia; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This analysis aims to analyze and evaluate the application of risk management to UMKM OUR DéJAHOE in facing the challenges of competitive and dynamic slow fashion industry. Descriptive qualitative research methods are used with the ISO 31000:2018 standards-based approach. The identification results show 46 risks divided into four main domains: Market, Finance, Operations, and Human Resources. Through Likelihood's $×$ Impact assessment, it was found that the company's risk profile was dominated by the High (39%) and Medium (50%) categories. Critical risks concentrate on market threats from fast/preloved fashion competitors (R02, R04) and operational bottlenecks caused by a single dependence on major suppliers and tailors (R30, R38). These issues are exacerbated by global conditions such as a decrease in purchasing power (R03) and an increase in raw material prices (R18). Risk treatment recommendations include mitigation strategies such as diversification of supply chains, strengthening brand differentiation (brand identity), and optimization of working capital (R16, R17). This study concluded that the implementation of ISO 31000:2018 is vital for the sustainability of low fashion MSMEs amid a market landscape that demands quality, ethics, and price competitiveness.